Missing [C ii] emission from early galaxies. Issue 4 (14th October 2020) - Carniani, S; Ferrara, A; Maiolino, R; Castellano, M; Gallerani, S; Fontana, A; Kohandel, M; Lupi, A; Pallottini, A; Pentericci, L; Vallini, L; Vanzella, E
ABSTRACT: ALMA observations have revealed that [C ii ] 158 μ m line emission in high- z galaxies is ≈2–3 × more extended than the UV continuum emission. Here we explore whether surface brightness dimming (SBD) of the [C ii ] line is responsible for the reported [C ii ] deficit, and the large L_[O III]/L_[C II] luminosity ratio measured in early galaxies. We first analyse archival ALMA images of nine z > 6 galaxies observed in both [C ii ] and [O iii ]. After performing several uv -tapering experiments to optimize the identification of extended line emission, we detect [C ii ] emission in the whole sample, with an extent systematically larger than the [O iii ] emission. Next, we use interferometric simulations to study the effect of SBD on the line luminosity estimate. About 40 per cent of the extended [C ii ] component might be missed at an angular resolution of 0.8 arcsec, implying that L_[C II] is underestimated by a factor ≈2 in data at low (<7) signal-to-noise ratio. By combining these results, we conclude that L_[C II] of z > 6 galaxies lies, on average, slightly below the local L_[C II]- SFR relation (Δ z = 6–9 = −0.07 ± 0.3), but within the intrinsic dispersion of the relation. SBD correction also yields L_[O III]/L_[C II]10, i.e. more in line with current hydrodynamical simulations.